2020
DOI: 10.1016/j.asmr.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Graft Options in Anterior Cruciate Ligament Reconstruction: A Systematic Review and Network Meta-Analysis

Abstract: Purpose To evaluate the effectiveness of various graft options for anterior cruciate ligament reconstruction using network meta-analysis. Methods A medical literature search was conducted of PubMed, the Cochrane Library, Embase, SCOPUS, and Web of Science from their inception through March 1, 2019. The outcomes, including International Knee Documentation Committee (IKDC) form, Lachman test, Lysholm score, Pivot shift test, and Tegner score, were evaluated among graft op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 78 publications
(263 reference statements)
1
12
0
1
Order By: Relevance
“…In recent years, a number of systematic reviews and meta-analyses have evaluated different aspects of ACLR surgery as well as instructional reviews 72 and practice guidelines. 73 In their review of graft options, Mo et al 74 evaluated 45 RCTs and found that patellar tendon autograft was most appropriate in terms of IKDC and Lachman test results. Wang et al 75 evaluated 11 RCTs comparing clinical outcomes and adverse events associated with irradiated and nonirradiated allografts in ACLR and found no significant differences between autograft and nonirradiated allograft, although autograft offered greater advantages in functional outcomes and adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of systematic reviews and meta-analyses have evaluated different aspects of ACLR surgery as well as instructional reviews 72 and practice guidelines. 73 In their review of graft options, Mo et al 74 evaluated 45 RCTs and found that patellar tendon autograft was most appropriate in terms of IKDC and Lachman test results. Wang et al 75 evaluated 11 RCTs comparing clinical outcomes and adverse events associated with irradiated and nonirradiated allografts in ACLR and found no significant differences between autograft and nonirradiated allograft, although autograft offered greater advantages in functional outcomes and adverse events.…”
Section: Discussionmentioning
confidence: 99%
“… 73 In their review of graft options, Mo et al . 74 evaluated 45 RCTs and found that patellar tendon autograft was most appropriate in terms of IKDC and Lachman test results. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…7,10 A multitude of studies have evaluated advantages and disadvantages of each graft, but generally there is higher donor site morbidity, larger incisions, possible violation of the extensor mechanism, and increased surgical times with autografts, whereas there is a higher failure rate in patients <25 years old; an increased risk of infection, disease transmission, and cost; and reduced graft strength with allograft selections. [7][8][9]11 BTB autograft is preferred in the senior author's clinical practice of >35 years, especially for patients involved in high-level athletic competition; however, the role of BTB autograft versus allograft in older, less high-demand individuals is less clearly defined. The senior author experienced allograft BTB usage increasing at 5-year increments since 1986 of 1%, 3%, 13%, 24%, and >50%.…”
mentioning
confidence: 99%
“…Although BTB autograft is considered the gold standard for primary ACL reconstruction 7 , 8 , 9 among high-volume ligament surgeons, particularly those who take care of intercollegiate, professional, and elite-level athletes, many factors should be considered before definitive selection. These include age, desired activity level, quality of host tissue, gender, concurrent injuries, risk of donor site morbidity, cosmesis, and desired type of graft fixation.…”
mentioning
confidence: 99%
See 1 more Smart Citation